The Relationship Between The Use Of The Takoboto Application And The Ability To Memorize Kanji At The Natsuka Gakkou Padang Japanese Language Course Institution - Rukmana, Elva Ayu; Ismaniar, Ismaniar (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
This research was motivated by the less than optimal use of learning media and the difficulty of students learning Japanese grammar at the Natsuka Gakkou Japanese Language Course Institute. The aim of this research is to determine the description and relationship between the use of the takoboto media application and the ability to memorize kanji at the Natsuka Gakkou Japanese Language Course Institute in Padang. This research uses a correlational quantitative approach. The population of this study was all 23 students of the Japanese language course Natsugakkou Padang who were studying kanji for level 1 and 2 classes. The sampling technique in this research was carried out using the target sampling method, so that the total sample that the researcher took was 80% of the population, namely 18 students at the Natsuka Gakkou Japanese Language Course Institute. The data collection technique in this research is a questionnaire. The data analysis method in this research is the Spearman rank correlation method. The results of this research are: 1.) The use of the takoboto application media at the Natsuka Gakkou Padang Japanese Language Course Institute is still relatively low, this is evident from the students who were respondents in this research more often answering disagree (KS). 2.) The ability to memorize kanji at the Natsuka Gakkou Japanese Language Course Institute in Padang, there are still many students who do remedial work because they do not reach the target kanji given. In the learning process, the measure of student success can be seen from their grades and 3.) 3. There is a significant relationship between the use of the takoboto application media and the ability to memorize kanji at the Natsuka Gakkou Japanese Language Course Institute in Padang. By proving rcount from rtable, the hypothesis is accepted.